Shallow water seafloor inversion using ship-generated striation patterns - Clarke, P.; Jones, Adrian (na, 2012)
The accuracy of transmission loss model predictions in a shallow water environment is typically highly dependent on the acoustic reflectivity of the seafloor. Using sediment type databases can help determine the seafloor reflectivity, but a lack of data and conversion to acoustic properties limits reflectivity estimation accuracy. A method of inferring the seafloor reflectivity from the striation pattern produced by a ship as it transits past a hydrophone is demonstrated. This method expands on a technique devised previously (Jones and Clarke, Proceedings of 20th Intl. Congress on Acoustics, ICA 2010) in which seafloor reflectivity was inferred from multi-path interference of broadband, including impulsive, transmissions. This paper discusses the application of the striation-based method to ship data obtained from a trial conducted in shallow water off Perth, Western Australia. This includes comparisons of measured transmission loss with transmission loss model predictions using (i) sediment grabs, (ii) the impulsive inversion technique, and (iii) the striation-based inversion technique.